The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1021/bi6024897
|View full text |Cite
|
Sign up to set email alerts
|

A Mass Spectrometric Study on the in Vitro Methylation of HMGA1a and HMGA1b Proteins by PRMTs:  Methylation Specificity, the Effect of Binding to AT-Rich Duplex DNA, and the Effect of C-Terminal Phosphorylation

Abstract: HMGA1a and HMGA1b are members of one subfamily of non-histone chromosomal highmobility group (HMG) proteins. They bind to various DNA-related substrates, including the minor groove of AT-rich duplex DNA sequences, and have been postulated to be architectural transcription factors functioning in a wide variety of cellular processes. Post-translational modifications of HMGA1 proteins, such as phosphorylation, acetylation, and methylation, are widely observed in tumor cells in vivo and correlated with the modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 56 publications
(137 reference statements)
1
34
0
Order By: Relevance
“…Arginine methylation in this region thus probably plays an important role in HMGA functions. All findings on methylation of the HMGA1 proteins on different Arg residues were very recently confirmed and extended by Zou et al (67).…”
Section: Long-range Chromatin Interactionssupporting
confidence: 69%
“…Arginine methylation in this region thus probably plays an important role in HMGA functions. All findings on methylation of the HMGA1 proteins on different Arg residues were very recently confirmed and extended by Zou et al (67).…”
Section: Long-range Chromatin Interactionssupporting
confidence: 69%
“…In this context, Sgarra et al [88] reported that the methylation occurs on Arg-25 in the first AT-hook, and later we found that the same site, i.e., Arg-25, can be both mono-and dimethylated in PC-3 human prostate cancer cells. In addition, both isoforms of dimethylation, i.e., symmetric and asymmetric dimethylation, were detected [90]; the asymmetric and symmetric dimethylarginines were assessed by MS/MS based on characteristic neutral losses from the side chains of the modified arginines [90][91][92].…”
Section: Ptms Of Hmga Proteinsmentioning
confidence: 99%
“…PRMT6 exhibits a relatively narrow substrate specificity, with the currently known substrates being HMG1A (66,87,106), histone subunits (32,37,38), DNA polymerase beta (20), and several components of the HIV virus (10, 39, 40) as well as PRMT6 itself (28). The human enzyme is reported to display an exclusively nuclear localization pattern (28), consistent with its known roles in…”
mentioning
confidence: 99%